ChemInform Abstract: Structural, Magnetic and Theoretical Investigations on the Magnetocaloric Properties of La0.7Sr0.25K0.05MnO3 Perovskite. Issue 39 (8th September 2016) - El Kossi, S.; Dhahri, J.; Hlil, E. K.
Abstract: The title compound is synthesized by solid state reaction of La2 O3, SrCO3, K2 CO3, and MnO2 (calcination at 900—1100 °C, sintering at 1200 °C for 24 h).